Clinical characteristics of low‐grade tumor‐related epilepsy and its predictors for surgical outcome. Issue 7 (31st May 2021) - He, Chenmin; Hu, Lingli; Chen, Cong; Zheng, Zhe; Jin, Bo; Ding, Yao; Wang, Shuang; Ding, Mei‐Ping; Zhu, Junming; Wang, Shan
Abstract: Objectives: Low‐grade tumors are the most common neoplasms inducing focal epilepsy; however, the short‐ and medium‐term efficacy of surgery in epilepsy patients with low‐grade tumors remains underappreciated. This study aims to summarize the clinical characteristics of epilepsy patients with low‐grade tumors and to identify factors associated with postsurgical seizure‐free outcomes. Methods: We retrospectively reviewed consecutive patients with low‐grade tumors who underwent subsequent epilepsy surgery in our epilepsy center, between 2012 and 2018 with a minimum follow‐up of 1 year. Using Engel's classification and Kaplan–Meier survival analysis, we assessed postoperative seizure freedom over time. Demographical, electroclinical, and other presurgical evaluations were then evaluated for association with postoperative seizure outcome. Results: The cohort included a total of 132 patients: 79 males and 53 females. Among them, 110 (83.33%) were seizure‐free through their last follow‐up. The Engel class I outcomes were 90.15%, 87.76%, 85.53%, 82.46%, and 73.17% at the end of the 1st, 2nd, 3rd, 4th, and 5th postoperative years, respectively. Multivariate logistic analysis revealed that longer epilepsy duration ( p < 0.001, OR 1.091, 95% CI 1.040–1.144) and incomplete resection ( p = 0.009, OR 3.673, 95% CI 1.393–9.684) were independently associated with seizure recurrence through the last follow‐up. Conclusions: Surgical treatment for seizure control in patients with low‐grade tumors provides excellent short‐ and median‐term outcomes.